(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the modern era of digitalization, education systems are undergoing rapid transformations, and one of the most significant developments is the integration of information and communication technologies (ICT) into the teaching and learning process. Computer science, as a discipline that directly deals with technology, is highly influenced by the application of ICT tools in classrooms. The effective use of these technologies not only simplifies the process of explaining complex concepts but also enhances students’ motivation and engagement.